HZ. OSMAN`IN DEVLET POLİTİKASI VE VALİLERİ - KESKİN, HASAN (Fırat Üniveristesi, 2001)
Yüksek Lisans Tezi HZ. OSMAN'IN DEVLET POLİTİKASI VK VALİLERİ Hasan KESKİN FIRAT ÜNİVERSİTESİ SOSYAL BİLİMLER ENSTİTÜSÜ İSLAM TARİHÎ VE SANATLARI ANA BİLİM DALI İSLAM TARİHİ BİLİM DALI 2001, Sayfa,93 "Hz- Osman 'im Devlet Politikası ve Valileri " adı altında gerçekleştirilen bu araştırma giriş ve iki bölümden oluşmaktadır. Giriş bölümünde Hz. Ebu Bekir'in döneminden Hz. Osman'ın halifeliğine kadar ana hatlarıyla bilgi verilmiştir. Birinci bölümde Hz. Osman'ın soyu,doğumu,müslüman oluşu, halifeliği ve dönemindeki fetihleri hakkında bilgi sunulmuştur. İkinci bölümde ise, Hz. Osman'ın dönemimdeki sosyal faaliyetler^siyasi olaylar, devlet yönetimi, tayin ettiği valilerin idareleri ve hayatları hakkında bilgi verilmiştir. Yaptığımız araştırma sonucunda Hz. Osman'ın devlet yönetiminin dönemin şartlarına hitap edemediği yetersiz geldiği ve tayin ettiği komutan, vali gibi üst düzey yöneticilerin kendi akrabalarından olduğu tespit edilmiş olup; bu yöneticilerin bazılarının tecrübesiz, zühd ve takvadan uzak, halka sert davranan, onların müşkülerini çözmeye çalışmayan kendi t..?;;(;-' doğrultusunda r»?reW eden kişiler olduğu gözlenmiştir. Neticede ' plıımda f»V;;. ; 'O

SUMMARY MASTER THESESIS THE STATE POLICY OF THE CALİGH OSMAN AND THE LIVES OF HIS GOVERNORS Hasan KESKİN The University Of Fırat Social Sciences institute Main Science Branch Of Islamic History 200 1, Page: 93 This paper that called "The State Policy Of Caligh Osman And The Lives Of His Governors''' is consist of an introduction and two sections. Tn Introduction part information has been given from the period of the last caligh Ebu Bekir to the caliphate of caligh Osman in main lines. In the first section information has been given about the caligh Osman's birth, race, how he had been a muslim, his caliphate and conquests in his period. In contrast to first section, in the second section information has been given about the social activities, political events, state governing, the administration of the governors that the caligh Osman appointed to and the lives of these appointed governors in the period of the caligh Osman At the end of the research we had done, we have determined that the state administration of the caligh Osman didn't adress to the circumstances of that period and was inadequate. We have also determined that top most administrators such as commanders and governors that the caligh Osman appointed were his relatives and some of these governors were inexperienced, far from god - fearing behavior and didn't behaved well to the public. We have obsorved that those governors were those who acted according to their benefits Consequently, hidden intended people benefiting from administrative emptiness in ~T">t" V'^e^ the mli«h Osman. The cali eh Osman died for islam.
The State policy of caligh Osman and the lives of his governors
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Din; Religion